2021
DOI: 10.3390/jcm11010080
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Body Composition Parameters and Phase Angle as Related to Lifestyle among Young People

Abstract: The aim of the study was to indicate which body composition parameters and which lifestyle components affect the phase angle (PA) value in young adults. Two-hundred-and-eighty-one students at Wroclaw Medical University participated in the study. A survey on respondent lifestyles was followed by anthropometric measurements, body composition analysis, and basal metabolic rate (BMR) calculation. The differences in the body composition of men and women corresponded to their sexual anatomy and physiology. Sex-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
3
8
0
Order By: Relevance
“…Furthermore, a decrease in muscle mass is associated with a decrease in PhA values [ 30 ], which is in line with the results presented in this study. Similarly to our results, Jaremkow et al reported that PhA values positively correlated with fat-free mass, muscle mass and muscle percentage, whereas negative correlations were determined for fat mass and fat percentage [ 31 ]. On the other hand, Curvello-Silva found no correlation between PhA and body composition parameters in severely obese patients [ 9 ].…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, a decrease in muscle mass is associated with a decrease in PhA values [ 30 ], which is in line with the results presented in this study. Similarly to our results, Jaremkow et al reported that PhA values positively correlated with fat-free mass, muscle mass and muscle percentage, whereas negative correlations were determined for fat mass and fat percentage [ 31 ]. On the other hand, Curvello-Silva found no correlation between PhA and body composition parameters in severely obese patients [ 9 ].…”
Section: Discussionsupporting
confidence: 91%
“…The two main barriers for PA identified by medical students are lack of time and stress [23,33]. Jaremkówet al [24] concucted a study among medical and dentistry students in Poland and indicate that, similar to our results, male students spent more time on both PA/exercise significantly more often than female students. In a study conducted among health science students in Spain, Romero-Blanco et al [25] evaluated the level of PA of male and female students before and during the coronavirus lockdown, and showed that female students have a significant increase levels of PA in relation to male students.…”
Section: Discussionsupporting
confidence: 85%
“…Irregular PA is more common in people of better socioeconomic status, people of rural origin, it is associated with alcohol, tobacco and drug abuse, negative social impact (family, peers, social media, etc. ), as well as overweight and obesity [4,5,13,20,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, a dietary pattern rich in potatoes and animal proteins (meat and poultry) was positively related to PhA. Interestingly, PhA has recently been reported to be positively associated with meat consumption [ 22 ], while it seems to increase after a ketogenic diet independent of weight loss [ 23 ]. Of course, in our study, it was mostly a high-protein dietary scheme, rather than a ketogenic pattern that was a significant determinant of PhA.…”
Section: Discussionmentioning
confidence: 51%